2020
DOI: 10.3892/etm.2020.8459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DEC1 on the proliferation, adhesion, invasion and epithelial‑mesenchymal transition of osteosarcoma cells

Abstract: Differentiated embryonic chondrocyte-expressed gene 1 (DEC1) is associated with various types of human cancer; however, there is limited data regarding the functions of DEC1 in osteosarcoma. The present study aimed to examine the expression of DEC1 in human osteosarcoma tissues and cell lines. Furthermore, the effects of DEC1 on the proliferation, adhesion, invasion and epithelial-mesenchymal transition (EMT) of osteosarcoma cells were investigated. Using reverse transcription-quantitative PCR and western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The expression of E-cadherin was closely inversely related to the expression of N-cadherin, which predicted the malignant potential and invasiveness of osteosarcoma cell lines [27][28][29]. Several studies in this article concluded that upstream modification of E-cadherin expression can determine a tumor cell line's invasiveness and is associated with the severity of cancer and tumor cell survival [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of E-cadherin was closely inversely related to the expression of N-cadherin, which predicted the malignant potential and invasiveness of osteosarcoma cell lines [27][28][29]. Several studies in this article concluded that upstream modification of E-cadherin expression can determine a tumor cell line's invasiveness and is associated with the severity of cancer and tumor cell survival [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin expression modification has been explored as a target for therapy in multiple disease processes. In the results, multiple in vitro studies displayed a decrease in tumor malignancy and invasive potential with an increase in E-cadherin expression and a decrease in N-cadherin expression via transfection with silencing or micro RNAs targeted to upstream effectors [ 2 , 12 , 16 , 20 , 24 , 25 , 33 , 34 ]. Bi et al utilized an in vivo murine model to transfect endometrial cells with homeobox proteins that resulted in downstream upregulation of E-cadherin, improving embryo adhesion and implantation [ 46 ].…”
Section: Reviewmentioning
confidence: 99%
“…As previously described [ 24 ], the transfected MG63 and Saos2 cells were trypsinized and inoculated into 96-well plates (2 × 10 3 cells/well), and then the cells were routinely cultured. Subsequently, on days 0, 1, 2, 3 and 4, each well was added with 10 μL of 5 mg/mL MTT solution (Beyotime Biotechnology, Shanghai, China), and the cells were incubated in 5% CO 2 for 4 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Differentiated embryo-chondrocyte expressed gene 1 (DEC1) is a structurally unique basic helix-loophelix (bHLH) protein which is a major regulator of a variety of physiological and pathological processes, including circadian rhythms, hypoxia, cellular proliferation, apoptosis, immunity, and inflammation [18][19][20][21][22] . Initially being identified in human chondrocytes, DEC1 is closely linked to bone growth and remodeling [23] .…”
Section: Introductionmentioning
confidence: 99%